Lung inflammatory pattern and antibiotic treatment in pneumonia. Issue 1 (December 2015) - Lorenzo, María-José; Moret, Inés; Sarria, Benjamín; Cases, Enrique; Cortijo, Julio; Méndez, Raúl; Molina, Jose; Gimeno, Alejandra; Menéndez, Rosario
Abstract Background In community-acquired pneumonia host inflammatory response against the causative microorganism is necessary for infection resolution. However an excessive response can have deleterious effects. In addition to antimicrobial effects, macrolide antibiotics are known to possess immunomodulatory properties. We aimed to evaluate inflammatory cytokine profiles – both locally (bronchoalveolar lavage) and systemically (blood) – in community-acquired pneumonia admitted patients after at least 72 hours of antibiotic treatment (with and without macrolide containing regimens) and requiring bronchoscopic examination for inadequate response due to infection progression and/or lack of clinical stability. Methods A prospective study was performed on 52 admitted patients who developed an inadequate response after 72 hours of antibiotic treatment - non-responders community-acquired pneumonia - (blood and bronchoalveolar lavage), and two control groups: 1) community-acquired pneumonia control (blood) and 2) non-infection control (blood and bronchoalveolar lavage). Cytokine profiles (interleukin (IL)-6, IL-8, IL-10), tumour necrosis factor α and clinical outcomes were assessed. Results Non–responders patients treated with macrolide containing regimens showed significantly lower levels of IL-6 and TNF-α in bronchoalveolar lavage fluid and lower IL-8 and IL-10 in blood than those patients treated with non-macrolide regimens. Clinical outcomes showed that patients treated with macrolide regimens required fewer days to reach clinical stability (p < 0.01) and shorter hospitalization periods (p < 0.01). Conclusions After 72 hours of antibiotic effect, patients who received macrolide containing regimens exhibited lower inflammatory cytokine levels in pulmonary and systemic compartments along with faster stabilization of infectious parameters.